RFID-sensor based multi-reader cooperation mechanism information collecting protocol in IOT - Wen-xiu LI; Ya-hong GUO; Jin-bao LI; Long-jiang GUO; Shao-bin ZHANG (Tongxin xuebao)
In order to collect the information of sensor nodes in multi-reader environment, the MRCIC information col-lection protocol was proposed. MRCIC information collection protocol uses the previous time slot position to assign the slot position where tags replied, and save the execution time of identifying the interrogated tags efficiently. Because of reader collisions problem, the intersecting regions tags couldn't be detected. Hence, in order to detecting them, MRCIC adopts the method that readers which did not have intersecting regions transmit interrogation information simultaneously and other readers sleep, to collect the intersecting regions tags' information. It improves the accuracy of lection. Theoretical analysis and experimental results show that MRCIC gets shorter delay than AMDCU、ALOHAinformation、BTcol-and PIC, and it can reach the significantly accuracy rate.